Part A: iterative addition of carbon nucleophiles to N,N-dialkyl carboxamides for the synthesis of α-tertiary amines; Part B: asymmetric synthesis of alkylzincs by rhodium-catalyzed enantioselective arylative cyclization of 1,6-enynes with arylzincs - Chen, Jiahua (Nanyang Technological University, 2022)
This thesis contains two parts. Part A (Chapters 1 and 2) describes the synthesis of α-tertiary amines by iterative addition of carbon nucleophiles to N,N-dialkyl carboxamides, and Part B (Chapters 3 and 4) describes the rhodium-catalyzed enantioselective arylative cyclization of 1,6-enynes with arylzincs for the synthesis of chiral alkylzincs. Chapter 1 provides a general overview of the synthesis of amines by nucleophilic attack of carboxamides. It covers the addition of hydride (reductive functionalization) and the addition of carbanions. Chapter 2 describes a new protocol for the synthesis of α-tertiary amines by iterative addition of carbon nucleophiles to N,N-dialkyl carboxamides. Employment of (trimethylsilyl)methylmagnesium chloride as the second nucleophile resulting in the formation of 1,1-diarylethylenes via aza-Peterson olefination. Chapter 3 provides an introduction to rhodium-catalyzed carborhodation of alkynes and the cascade reactions of the organorhodium intermediates. Chapter 4 describes an asymmetric synthesis of 2-(alkylidene)cyclopentylmethylzincs with high enantioselectivities by a chiral diene/rhodium-catalyzed arylative cyclization of 1,6- enynes with arylzincs. The enantioenriched alkylzincs were readily converted in a one-pot approach into a wide variety of functionalized products. Chapter 5 lists the experimental data for chapters 2 and 4.